“I can't get no satisfaction!” The critical role of political skill for workplace status and career satisfaction in grandiose narcissism - Franziska Böhm; Gerhard Blickle (Acta Psychologica)
This study extends socioanalytic and self-control theory to grandiose narcissism in the vocational career context with a special focus on attained workplace status and career satisfaction. In a sample of N = 406 target–coworker multisource datasets, and target workers with several decades of vocational experience, grandiose narcissism assessed with the Five-Factor Narcissism Inventory negatively relates to workplace status, and indirectly to career satisfaction via workplace status, when political skill is low. However, good political skill enables individuals on the higher end of the grandiose narcissism scale to control their antagonistic behavioral tendencies and present their agentic ambitions in a more appropriate manner, mitigating the negative (indirect) association with workplace status and career satisfaction. In sum, we hypothesized and found that with low political skill, grandiose narcissism is negatively associated with career satisfaction via reduced workplace status.